Investigating the Relationship Between Environmental Concern and Waste Management in Tourism - Roghayeh Ghorbani; Tahmaseb Talebi; Mohammad Taghipour (International Journal of Climate Conditions, 2024)
Tourism can bring both positive and negative effects in terms of the environment, which is the prevention of negative effects, including the necessity to preserve the environmental and even cultural, social resources of touristic areas. The purpose of this research is to investigate the relationship between environmental concerns and waste management in Damavand mountain tourism areas in 2017. This study was carried out as a survey and is of the descriptive-analytical variety. In this research, the samples were selected as available among tourists, travelers and mountaineers in Damavand mountains in the number of 224 people in 2017. The researcher developed the questionnaire utilized in this study, which comprised 35 items on a 5- and 3-option Likert scale. After preparing the questionnaire and verifying its face validity by experts in this field, the reliability of the questionnaire was measured and it was equal to 0.81. Regression analysis was used to analyze the data using SPSS version 22 software. In this study, 116 people (51.8%) were women and 108 people (48.2%) were men with bachelor's education level and above for more than 50% of all people. Based on the results of the regression analysis, it was found that the "environmental concern" component had a significant role in waste management (P-value<0.05). Based on the results of the research, it can be stated that if proper planning is done on the behavior of tourists and efforts are made to improve them, it will certainly have a significant impact on waste management in mountainous areas.
Keywords: Environmental concern; Tourism; Waste management; mountain areas; regression analysis